Poly(vinyl alcohol) hydrogel coatings with tunable surface exposure of hydroxyapatite - Moreau, David (Landes Bioscience, 2014)
Insufficient bone anchoring is a major limitation of artificial substitutes for connective osteoarticular tissues. The use of coatings containing osseoconductive ceramic particles is one of the actively explored strategies to improve osseointegration and strengthen the bone-implant interface for general tissue engineering. Our hypothesis is that hydroxyapatite (HA) particles can be coated robustly on specific assemblies of PVA hydrogel fibers for the potential anchoring of ligament replacements. A simple dip-coating method is described to produce composite coatings made of microscopic hydroxyapatite (HA) particles dispersed in a poly(vinyl alcohol) (PVA) matrix. The materials are compatible with the requirements for implant Good Manufacturing Practices. They are applied to coat bundles of PVA hydrogel fibers used for the development of ligament implants. By means of optical and electronic microscopy, we show that the coating thickness and surface state can be adjusted by varying the composition of the dipping solution. Quantitative analysis based on backscattered electron microscopy show that the exposure of HA at the coating surface can be tuned from 0 to over 55% by decreasing the weight ratio of PVA over HA from 0.4 to 0.1. Abrasion experiments simulating bone-implant contact illustrate how the coating cohesion and wear resistance increase by increasing the content of PVA relative to HA. Using pullout experiments, we find that these coatings adhere well to the fiber bundles and detach by propagation of a crack inside the coating. These results provide a guide to select coated implants for anchoring artificial ligaments.